A Study on Balance of Payment in India and Its Importance & Justification: Analyzing the Role of Balance of Payments in India's Economic Development (Journal of Advances and Scholarly Researches in Allied Education, 2017)
India has become the fastest growing economy in the world. The balance of payments represents the transactions of economy and plays essential role in determining the position of an economy. International trade is vital for all nations over the world. Trade stimulates the growth of various sectors of economy. The growth of economy depends on the exports and imports as these increases the foreign currency which leads to the overall development.